1995
DOI: 10.1021/jo00114a035
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide as a Phosgene Replacement: Synthesis and Mechanistic Studies of Urethanes from Amines, CO2, and Alkyl Chlorides

Abstract: Several carbamate esters were synthesized from amines, carbon dioxide, and alkyl chlorides. The effect of added hase on the yield and selectivity of carbamate ester formation was found to be highly important with the use of sterically hindered guanidine bases giving the best results. Relative rate studies were carried out giving the following order of reactivity between carbamate anions in acetonitrile with benzyl chloride giving carbamate esters:Rate studies were carried out with the diethyl, s-butyl, phenyl,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(112 citation statements)
references
References 0 publications
6
105
0
1
Order By: Relevance
“…at 25 °C and 1 bar was bubbled through the amine solutions for 30 min using a stainless steel needle to ensure complete conversion of (4) to benzylcarbamic acid (5). Samples analyzed via 13 C NMR at room temperature and pressure.…”
Section: Synthesis Of Benzylcarbamic Acid (5)mentioning
confidence: 99%
See 2 more Smart Citations
“…at 25 °C and 1 bar was bubbled through the amine solutions for 30 min using a stainless steel needle to ensure complete conversion of (4) to benzylcarbamic acid (5). Samples analyzed via 13 C NMR at room temperature and pressure.…”
Section: Synthesis Of Benzylcarbamic Acid (5)mentioning
confidence: 99%
“…It has been shown that amines readily react with CO2 to form a variety of products depending on the solvent and/or the presence of strong organic bases [4,5,9,25]. These CO2 adducts are, in principle, protected amines.…”
Section: In Situ Protection Of Amines With Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…Carbamate is thermally unstable and equilibrated between CO 2 and corresponding amine upon heating. 19,36,37 This can be useful for the capping of growing AgNPs with carbamic acid as a stabilizer. Therefore, 2-ethylhexylammonium 2-ethylhexylcarbmate (EHAEHC) reacted with the surfaces of Ag-NPs during thermal reduction.…”
Section: 35mentioning
confidence: 99%
“…Organic and inorganic bases, crown ethers, and cryptands [63][64][65][66] catalyze this reaction. However, these homogeneous catalysts will cost extra energy and effort to be separated from the product.…”
Section: 62mentioning
confidence: 99%